Analisis Rencana Pelaksanaan Pembelajaran (RPP) Biologi Berkarakter Kelas XI SMAN Untuk Standarisasi RPP Di Kota Pariaman - Aflimardia, Aflimardia; Risdawati, Renny; Mulyati, Mulyati (STKIP PGRI Sumbar, 2013)
ABSTRACT Lesson Plan (RPP) is essentially a short-term plan for estimating or projecting what will be done in learning process. However, those found in the field that the teacher lesson plan created by the lack of in accordance with the demands of the curriculum. For the analysis of the RPP semester II of eleventh grade biology teacher at SMAN Pariaman using RPP assessment instruments that have been developed from the IPKG-1. The purpose of this study was to determine whether the lesson plan created by the teacher in class XI of semester II SMAN in Pariaman is in conformity with the standards IPKG-1 which has been developed. This research is a descriptive study. Sampling technique in this study was stratified random sampling method is random based strata. Samples taken are 4 schools and one teacher of biology class XI of SMAN sampled. Sampling technique teacher is simple random sampling. The sampled schools were SMAN 1, 2, 3 and 4 Pariaman. Analytical results for the percentage of RPP assessment instrument for Pariaman is enough standard with a value percentage 63, 3% while the results of the analysis for completeness percentage is less standard components of RPP with percentage value of existing components is 55, 75% and the another percentage of components is not that is 44, 25%.